BIOSYNTHESIS OF SILVER NANOPARTICLES USING AQUEOUS BROCCOLI EXTRACT- CHARACTERIZATION AND STUDY OF ANTIMICROBIAL, CYTOTOXIC EFFECTS. - G.CAROLING; TIWARI, SUNITA KUMARI; RANJITHAM, A.MERCY; R.SUJA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
OBJECTIVEâ€“ The synthesis of metal nanoparticles is a growing area of research due to its potentiality in the application and development of advanced technologies. In general, nanoparticles are synthesized by using chemical methods which are not eco-friendly. Vegetable mediated synthesis of nanoparticles is a green chemistry approach that connects the nanotechnology and biotechnology. In the present investigation we report a green chemistry approach, for the biological synthesis of silver nanoparticles using Broccoli floret aqueous extract under optimum conditions METHOD- Here we have used a fast, convenient and environment friendly method for the synthesis of silver nanoparticles by biologically reducing AgNOâ‚ƒ with aqueous extract of Broccoli florets (Brassica Oleracea L. var. Italica) under optimum conditions (pH-6-7). The formation of silver nanoparticles was indicated by the colour change from colourless to reddish brown. Biosynthesized nanoparticles were characterized by UV-VIS, FT-IR, XRD, SEM, TEM and EDAX analysis. The free radical scavenging activity was assessed by DPPH assay. These biologically synthesised Ag nanoparticles were tested for antimicrobial activity against four human pathogens viz. Klebsiella Pneumonia, Staphylococcus Saprophyticus, Bacillus Cereus and Escheria Coli. These nanoparticles were assessed further for cytotoxic activity on MCF-7 cell line. RESULT-Â The reduction process was simple and convenient to handle and monitored by UV-Vis spectroscopy which showed surface plasmon resonance at 425nm. The presence of active proteins and phenolic groups present in biomass before and afterÂ reduction was identified by FT-IR. The crystalline morphology and size of the nanoparticles were determined by TEM, SEM AND X-ray diffraction studies, which showed the average particle size of silver nanoparticles was in the range 40- 50nm as well as revealed their FCC structure. Presence of elemental silver was revealed by EDAX analysis. These biologically synthesised Ag nanoparticles were found to be effective in controlling growth of human pathogens viz. Klebsiella Pneumonia, Staphylococcus Saprophyticus and Escheria Coli. These nanoparticles showed high percent toxicity against MCF-7 cell line. The reducing property of aqueous extract is due to the presence of antioxidant viz. ascorbic acid, polyphenols which is confirmed by quantitative assay and scavenging effect of free radicals proved by DPPH scavenging activity. CONCLUSION- The present investigation revealed that the fresh Broccoli floret aqueous extract is capable of producing silver nanoparticles that are quiet stable for 15 days at room temperature without any sign of precipitation. Keywords: Brassica oleracea L.var.italica, SEM, TEM, XRD, EDAX, FT-IR, Scherrer formula and Cytotoxic effect.